Strategi Manajemen Pelayanan Klinik Imam Bonjol dalam Menghadapi Persaingan Antar FKTP - Trianike Nor Aini; Agusta Dian Ellina (CV. Syntax Corporation Indonesia, 2021)
Indonesian citizens are obligated by law to participate in the JKN program via BPJS. The issue that develops is the intense competition for capitations among FKTPs, particularly private clinics. Imam Bonjol Clinic is one of Kediri City's private FKTP clinics. The threats and challenges include an unstable number of capitations, the emergence of new clinics, an often changing BPJS system, a budget that is increasingly in deficit, and frequent delays in the disbursement of capitation and non-capitation funds for BPJS. Carry out appropriate and effective clinical service management measures in response to these problems and threats. This method of research employed a qualitative descriptive approach to reflect a picture of a situation at a certain point in time. Purposive Sampling data collection methods included observation, document review, in-depth interviews with 17 respondents using semi-structured questions, and triangulation technically, time, and sources (3 sources included the Chairman of the Foundation, the Responsible Clinic, and BPJS employees). The results showed that the Internal Environment (Clinical Policy, Clinical Marketing Factors, Clinical Production Factors, Human Resources, Clinical Financial Factors, Service Management, Facilities and Infrastructure) and the External Environment influenced the implementation of Imam Bonjol’s clinical service management strategy in facing competition between FKTPs (Clinics, BPJS, Patients, Competitors, Nearby Communities). The most appropriate service management strategy for Imam Bonjol Clinic is the SO (Strength – Opportunities) strategy, which is a growth-oriented strategy that leverages the company’s existing opportunities and internal strengths via the Delphi method. Several marketing program recommendations for Imam Bonjol Clinic are expected to result from this strategy can improve health services in order to compete with FKTPs in the JKN era